1982
DOI: 10.1113/jphysiol.1982.sp014297
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypertonic solutions on quantal transmitter release at the crayfish neuromuscular junction

Abstract: SUMMARY1. The effects ofa hypertonic bathing medium, containing either NaCl or melezitose, on the average number (m) and the time course of quantal release following an action potential were studied using focal extracellular recording methods at synaptic sites on the opener muscle of the crayfish leg.2. After the application of hypertonic saline, the rate of spontaneous quantal release increased but m decreased to a new level within 1 min; the extent of depression depended on the magnitude of the increase in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
3
16
0
Order By: Relevance
“…The nIs52 array includes a construct with GFP fused to the lumenal terminus of the synaptic vesicle protein synaptobrevin, under the regulation of the unc-25 promoter, which is expressed in GABAergic neurons 17 . Primed vesicles can be induced to fuse with the plasma membrane in the absence of calcium influx by application of hyperosmotic media [21][22][23] , and the SNARE complex is required for vesicle fusion induced in this way 11 . To determine whether the docked vesicles we observed in electron micrographs were fusion competent, we applied hyperosmotic media to unc-13 mutants.…”
Section: Resultsmentioning
confidence: 99%
“…The nIs52 array includes a construct with GFP fused to the lumenal terminus of the synaptic vesicle protein synaptobrevin, under the regulation of the unc-25 promoter, which is expressed in GABAergic neurons 17 . Primed vesicles can be induced to fuse with the plasma membrane in the absence of calcium influx by application of hyperosmotic media [21][22][23] , and the SNARE complex is required for vesicle fusion induced in this way 11 . To determine whether the docked vesicles we observed in electron micrographs were fusion competent, we applied hyperosmotic media to unc-13 mutants.…”
Section: Resultsmentioning
confidence: 99%
“…Note added in proof. Niles & Smith (1982) studied the effects of hypertonic solutions on spontaneous and evoked quantal release at the crayfish neuromuscular junction. They found that hypertonic solutions, ranging from 04 to 1-3 Osm, decreased evoked output, m, but increased the rate of spontaneous quantal release.…”
Section: Discussionmentioning
confidence: 99%
“…This method of swelling is routinely used to reconstitute ion channels into planar membranes via fusion (Moczydlowski et al, 1985). In a wide range of biological secretory systems, osmoticants have been added to cells to shrink granules, and fusion has been inhibited (Niles and Smith, 1982;Zimmerberg and Whitaker, 1985;Holz, 1986).…”
Section: Introductionmentioning
confidence: 99%